The effect of arthropathies on illness perceptions, coping strategies, outcomes, and their changes over time in patients with inflammatory bowel disease: a 12-month follow-up study. Issue 4 (April 2018) - van Erp, Sanne J.H.; van der Have, Mike; Fidder, Herma H.; van der Heijde, Désirée; Wolterbeek, Ron; Hommes, Daniel W.; Kaptein, Ad A.; van der Meulen-de Jong, Andrea E.
Abstract : Objectives: Arthropathies are a common extraintestinal manifestation (EIM) in inflammatory bowel disease (IBD). This study evaluated the differences in illness perceptions, coping strategies, and illness outcomes between patients with IBD with and without arthropathies at baseline and examined changes at 12 months in these variables in patients with arthropathies. Methods: In total, 204 patients with ( n =123) and without ( n =81) arthropathies completed questionnaires at baseline and after 1 year, assessing illness perceptions, coping strategies, quality of life, and work and activity impairment. A linear regression analysis assessed the effect of arthropathies on these factors compared with patients without arthropathies. A mixed model analysis evaluated changes in illness perceptions, coping strategies, and outcomes in patients with arthropathies over time. Results: Patients with arthropathies had more persistent thoughts on symptomatology and the variability of symptoms, held more negative views on the effects of illness, had heightened emotions that affected daily functioning, and had a poorer understanding of IBD than patients without arthropathies. Patients with arthropathies could more efficiently divert attention, felt more useful to others, and perceived a reduced physical and mental health and an increased activity impairment compared with patients without arthropathies. At follow-up, patients with arthropathies were more sceptical about the effectiveness of medical treatment but were better able to adapt their activities to their complaints compared with baseline. Conclusion: Patients with arthropathies in IBD adopt different illness perceptions and coping strategies and have different outcomes compared with patients without arthropathies, which is important to know when designing behavioral and physical interventions to improve functioning.